Implementasi Metode Certainty Factor dalam Mengetahui Kerusakan Sepeda Motor Type Injeksi - Arjon Samuel Sitio; Fricles Ariwisanto Sianturi (Jurnal Sains dan Teknologi, 2021)
Motorcycles are the main means of transportation that many people use to support their activities. Before the development of technology, motorcycles still use carburetors. However, motorcycles that still use the carburetor system are still considered wasteful. With the development of technology, currently there is a Yamaha brand motorcycle with an injection system that is able to supply gasoline according to the engine's needs. Motorcycles with injection technology are much more efficient than motorcycles with carburetor technology, besides being economical, this type of motorcycle has reliable engine performance and power. However, there are often obstacles that cause damage to Yamaha injection motorcycles so that they interfere with user activities. An expert system is a system that adopts the expertise of an expert expert in a particular field into a computer system or program that is presented with a display that can be used by users who are not experts so that with this system users can make decisions or determine policies like an expert in solving problems. problem. The Certainty factor method is used to obtain the certainty value of the type of damage from an injection motorcycle expert, so that the user also gets a certainty value of damage from the selected symptoms from expert experience. The results of the diagnosis on the expert system that have been made that if the user checks for symptoms such as the engine stuttering when the gas is turned on, the electric starter is difficult/not lifting, the engine is difficult to start when using the kick starter, the exhaust often emits an explosive sound, it can be concluded from the results of the analysis that The damage is on the spark plug with a value of MB = 0.99, MD = 0.22 and a Certainty Factor value of 76.66%. The results of diagnostics that have been carried out by visitors or mechanics can be accessed again by entering the email in the database